Impact of food matrix components on nutritional and functional properties of fruit-based products - Oliveira, Ana (2018)
Nowadays, worldwide consumers seek delightful and appealing foods that are simultaneously safer, nutritional and healthier. Fruit-based products are largely consumed due to, in part, the consumer’s perception of these products as healthy and convenient perceived as similar or even with better health benefits than the raw fruits that originated them. However, it is of paramount importance to understand the impact of the food matrix components on nutritional and functional properties of fruit-based products. Isolated compounds, or fruit extracts are used more often than food products in interaction studies. These approaches do not consider the interferences of food matrix components and/or the impacts of food processing on bioactivity and bioaccessibility of the active compounds. In fact, the bioaccessibility of bioactive compounds can be different in diverse food matrices and this review aims to provide an integrated approach to the field of matrix interactions.